The anatomy, movement, and functions of human sperm tail: an evolving mystery. Issue 3 (25th November 2020) - Kumar, Naina; Singh, Amit Kant
Abstract: Sperms have attracted attention of many researchers since it was discovered by Antonie van Leeuwenhoek in 1677. Though a small cell, its every part has complex structure and different function to play in carrying life. Sperm tail is most complicated structure with more than 1000 proteins involved in its functioning. With the advent of three-dimensional microscopes, many studies are undergoing to understand exact mechanism of sperm tail movement. Most recent studies have shown that sperms move by spinning rather than swimming. Each subunit of tail, including axonemal, peri-axonemal structures, plays essential roles in sperm motility, capacitation, hyperactivation, fertilization. Furthermore, over 2300 genes are involved in spermatogenesis. A number of genetic mutations have been linked with abnormal sperm flagellar development leading to motility defects and male infertility. It was found that 6% of male infertility cases are related to genetic causes, and 4% of couples undergoing intracytoplasmic sperm injection for male subfertility have chromosomal abnormalities. Hence, an understanding of sperm tail development and genes associated with its normal functioning can help in better diagnosis of male infertility and its management. There is still a lot that needs to be discovered about genes, proteins contributing to normal human sperm tail development, movement, and role in male fertility. Sperm tail has complex anatomy, with surrounding axoneme having 9 + 2 microtubules arrangement along its entire length and peri-axonemal structures that contribute in sperm motility and fertilization. In future sperm tail-associated genes, proteins and subunits can be used as markers of male fertility. Abstract : Human sperm tail has a complex anatomy, and its every subunit (axonemal and peri-axonemal structures) plays a significant role in motility, male fertility; the sperm moves by spinning rather than simple swimming. It drills through the fluid in a corkscrew manner.